Antecedents and consequences of work stress at PT Borneo Etam Samudera in Bontang - Damayanti, Alfiana; Bharata, Wira; Hetami, Adietya Arie (Jurnal Ekonomi dan Bisnis, 2025)
This research has two objectives. The first objective is to describe compensation and the physical work environment which are predictors of employee work stress. Furthermore, this research will measure the impact of work stress on employee performance. The sample for this research is office employees and field employees, especially the bagging department (PPU) at PT. Borneo Etam Samudera with 57 respondents. The research method was carried out quantitatively and data collection used a questionnaire. The data in this research were analyzed using Partial Least Squares (PLS) with data analysis techniques based on Structural Equation Modeling (SEM). The research results show that all the proposed hypotheses are accepted. The results of this research prove that compensation and the physical work environment have a negative effect on employee work stress. On the other hand, the research results show that compensation and the physical work environment have a positive effect on employee performance. Work stress experienced by employees of PT. Borneo Etam Samudera is known to reduce their performance.